Between Feudalism and Islamic Boarding School Manners: A Literature Review - Enda Sri Wahyuni (CV. Kalimasada Group, 2025)
Purpose - This research aims to critically examine the use of the term feudalism in describing social relations in Islamic boarding schools and offers a conceptual redefinition that distinguishes between feudal power structures and Islamic ethical systems based on adab. Design/Methodology/Approach - With a qualitative-descriptive approach through the Systematic Literature Review, this study examines classical literature such as Ta'līm al-Muta'allim by Al-Zarnuji and Iḥyā' 'Ulūm al-Dīn by Al-Ghazali, as well as contemporary research on the social dynamics of Islamic boarding schools. Findings - The results of the study show that the hierarchical relationship between kiai and santri does not represent a pattern of domination as in feudalism, but a reflection of adab values that emphasize respect, sincerity, and the search for barokah. The social structure of pesantren is moral and pedagogical, not exploitative. In addition, this study emphasizes that adab values are in line with the goals of pesantren education as stated in Pasal 3 UU No. 18 Tahun 2019, That is, to form individuals who are faithful, knowledgeable, independent, and moderate. Originality/Value - The original value of this research lies in the synthesis of Western social theory and Islamic ethics which produces a new conceptual framework on the social relations of Islamic boarding schools, thus enriching the discourse of Islamic education in the context of modernization and democratization.